PENGARUH TERAPI SENTUHAN TERHADAP KENAIKAN BERAT BADAN PADA BAYI PREMATUR DI RSUD SIDIKALANG - Heriaty Berutu; Rugun Togianur Lingga; Wiwik Dwi Arianti (Jurnal Ilmiah Keperawatan IMELDA, 2025)
A premature baby is a baby born before 37 weeks of gestation. Generally, premature babies in Indonesia weigh less than expected and are at high risk of various health complications, including growth and developmental disorders, one of which is slow weight gain. The purpose of this study was to examine the effect of touch therapy on weight gain in premature babies at Sidikalang Regional General Hospital. The method was a correlational study with a one-group pre-test and post-test design. The population was 16 premature babies born in the Perinatology Ward of Sidikalang Regional General Hospital. Purposive sampling was used for sampling. The research instruments were the tools used for data collection. Data collection used standard operating procedures (SOP) for infant massage, infant massage equipment, and baby weight scales, as well as checklists. Statistical analysis used the Wilcoxon Signed Rank Test. The results showed an effect of infant massage therapy on weight gain in premature babies, with the Wilcoxon test showing a Z value of -3.535 and p = 0.000 (p < 0.00). Conclusion: There is an effect of infant massage therapy on weight gain in premature babies.